Analysis The Influence of Incentives and Islamic Workplace Spirituality on Employee Performance - Armina, Sheema Haseena; Kurnia, Rofif Hasan (Jurnal Ilmiah Ekonomi Islam, 2024)
Companies must be able to compete in the industrial era 4.0, where digitalization systems drive economic and business growth, to survive and achieve their goals optimally. The concept of human resources is increasingly important for the progress of the company due to the many developments that occur in the business and economic world in digitalization. Companies must improve the quality of their human resources by paying attention to the elements that contribute to improving employee performance, one of which is by paying attention to their welfare through policies on benefits, compensation, incentives, etc., and supported by a comfortable and conducive work environment. A comfortable work environment can be created through Islamic spirituality that makes employees feel the essence of work is to worship. To find out whether incentives and Islamic spirituality affect employee performance improvement, researchers are interested in conducting research at the Gontor Development Office, especially for employees who work there. This research is field research and uses quantitative methods with descriptive and inferential approaches using SPSS 23. The data used in this study are quantitative, namely primary data and secondary data, data collection techniques through observation, questionnaires, and documentation. The results of this study state that incentives and Islamic spirituality in the workplace have a simultaneous effect of 33.2% and Islamic spirituality is the most dominant variable affecting employee performance in the Gontor Construction Office